Associação do desempenho funcional de membros superiores com a força dos músculos rotadores do ombro e a resistência dos músculos do tronco em arremessadores adolescentes - Ferrer, Rafael Marques (2019)
The overhead throwing motion is a complex dynamic activity involving the entire body and this task requires high velocity, high load and a large range of motion with a high degree of precision. This task require a kinetic chain to transfer the force from lower limbs to the trunk and then to the upper limbs, thus allowing a optimum throwing performance. Appearing from this segment interdependence for throwing performance, the assessment of trunk and upper limb function in throwing athletes needs investigation, especially in the adolescent population. The first manuscript of this dissertation was a methodological study aimed at evaluating the reliability and validity of a video analysis of trunk muscle endurance tests in adolescents’ throwers. Fifty-nine male and female athletes between 15 and 18 years old participated. The isometric endurance time of extensor, anterior flexors and right/left lateral flexors trunk muscles which were evaluated by McGill Test by qualitative criterion (VISUAL) and quantitative by bidimensional kinematics analysis (GREATER ISOMETRY). We used Intraclass Correlation Coefficient for reliability, Pearson and Spearman correlation for validity, and Bland Altman plot for agreement. Video analysis using VISUAL or GREATER ISOMETRY criteria to assess trunk endurance in adolescents has excellent reliability and validity in identifying position changes during testing in adolescent athletes. However, these measures do not agree, so the methods are not equivalent. The second paper was an observational study aimed at comparing between genders and analyzing the relationship of trunk endurance and shoulder rotation strength with upper limb functional performance in adolescent throwers. Trunk endurance was assessed by the McGill test (VISUAL and GREATER ISOMETRY, shoulder rotation isometric strength by a hand-held dynamometer, and dominant upper limb functional performance by Y Balance Test Upper Quarter (YBTUQ) and Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) in 54 healthy handball and volleyball players, both gender. It was concluded that boys have higher trunk lateral flexor strength, shoulder rotation strength and power score by CKCUEST; and there is a relationship between extensor, lateral flexors trunk endurance, shoulder rotation isometric strength and dominant upper limb functional performance in adolescent throwers, mostly with height normalized CKCUEST scores.